A colorimetric, photothermal, and fluorescent triple-mode CRISPR/cas biosensor for drug-resistance bacteria detection - Laibao Zheng; Yayun Jiang; Fuyuan Huang; Qiaoli Wu; Yongliang Lou (Journal of Nanobiotechnology, 2023)
Abstract A multimodal analytical strategy utilizing different modalities to cross-validate each other, can effectively minimize false positives or negatives and ensure the accuracy of detection results. Herein, we establish a colorimetric, photothermal, and fluorescent triple modal CRISPR/Cas12a detection platform (CPF-CRISPR). An MNPs-ssDNA-HRP signal probe is designed to act as a substrate to trigger three signal outputs. In the presence of the DNA target, MNPs-ssDNA-HRP is cleaved by the activated CRISPR/Cas12a, resulting in the release of HRP and generating short DNA strands with 3-terminal hydroxyl on magnetic beads. The released HRP subsequently catalyzed TMB-H2O2 reaction and oxidized TMB is used for colorimetric and photothermal signal detection. Under the catalysis of terminal deoxynucleotidyl transferase (TdT), the remaining short DNA strands are used as primers to form poly-T and function as scaffolds to form copper nanoclusters for fluorescent signal output. To verify the practical application of CPF-CRISPR, we employed MRSA as a model. The results demonstrate the platform’s high accuracy and sensitivity, with a limit of detection of 101 CFU/mL when combined with recombinase polymerase amplification. Therefore, by harnessing the programmability of CRISPR/Cas12a, the biosensor has the potential to detect various drug-resistant bacteria, demonstrating significant practical applicability.